Mesothelioma risk after 40 years since first exposure to asbestos: a pooled analysis. Issue 9 (19th May 2014) - Reid, A; de Klerk, N H; Magnani, C; Ferrante, D; Berry, G; Musk, A W; Merler, E
Abstract : Background: The risk of malignant mesothelioma (MM) increases proportionally to the cumulative exposure, and to the 3rd or 4th power of time since first exposed, to asbestos. However, little is known about the risk of MM after more than 40 years since first exposure because most epidemiological studies do not have follow-up for sufficient periods of time. Methods: The data from six cohort studies of exposed workers and two cohorts with residential exposure have been pooled. A nested case control design matched cases and controls on calendar period and age. Conditional logistic regression modelled the relationship between time since first exposure and risk of MM. Results: The combined data consisted of 22 048 people with asbestos exposure (5769 women), 707 cases of pleural MM (165 in women) and 155 cases of peritoneal MM (32 in women). Median time since first exposure for pleural MM cases was 38.4 years (IQR 31.3–45.3). Median duration of exposure for pleural MM cases was 3.75 years (IQR 0.7–18.2). The rate and risk of pleural MM increased until 45 years following first exposure and then appeared to increase at a slower power of time since first exposure. The rate of increase in peritoneal MM over the 10–50 years since first exposure continued to increase. Conclusions: Exposure to asbestos confers a long-term risk of developing pleural and peritoneal mesothelioma which increases following cessation of exposure. While the rate of increase appears to start to level out after 40–50 years no one survives long enough for the excess risk to disappear.